2018
DOI: 10.1016/j.ejmech.2017.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Indole and Benzimidazole Bichalcophenes: Synthesis, DNA Binding and Antiparasitic Activity

Abstract: A novel series of indole and benzimidazole bichalcophene diamidine derivatives were prepared to study their antimicrobial activity against the tropical parasites causing African sleeping sickness and malaria. The dicyanoindoles needed to synthesize the target diamidines were obtained through Stille coupling reactions while the bis-cyanobenzimidazoles intermediates were made via condensation/cyclization reactions of different aldehydes with 4-cyano-1,2-diaminobenzene. Different amidine synthesis methodologies n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Synthesis of the bisnitrile compounds (5 a–n) . Sodium metabisulphite (1.14 g, 6 mmol) was added to a solution of the diamine 3 a – k (3 mmol) and the aldehyde 4 a – d (3 mmol) in DMSO (10 mL) and the mixture was heated at 140 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of the bisnitrile compounds (5 a–n) . Sodium metabisulphite (1.14 g, 6 mmol) was added to a solution of the diamine 3 a – k (3 mmol) and the aldehyde 4 a – d (3 mmol) in DMSO (10 mL) and the mixture was heated at 140 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…butan-1-amine (6). According to literature method [20], 15.00 g of o-phenylenediamine (138.00 mmol, 1.00 equiv.) in 80 mL of ethanol was added with ammonium chloride (0.74 g, 13.80 mmol, 10 mol%) as catalyst followed by gradual tipping of L-leucine (18.08 g, 138.00 mmol, 1.00 equiv.).…”
Section: Synthesis Procedures Synthesis Of 1-(1h-benzo[d]imidazol-2-ylmentioning
confidence: 99%
“…1. A very recent study showed DNA binding and antiparasitic properties of benzimidazole bichalcophenes [15].…”
Section: ■ Introductionmentioning
confidence: 99%
“…have created indispensable examples for development of new therapeutic agents . A great number of 2‐substituted benzimidazoles have been synthesized and their biological activities reported (Figure ) . A number of these studies has also focused on symmetrical and unsymmetrically substituted bis‐benzimidazoles .…”
Section: Introductionmentioning
confidence: 99%